2016
DOI: 10.1152/ajpcell.00285.2015
|View full text |Cite
|
Sign up to set email alerts
|

Muscle RANK is a key regulator of Ca2+ storage, SERCA activity, and function of fast-twitch skeletal muscles

Abstract: Receptor-activator of nuclear factor-κB (RANK), its ligand RANKL, and the soluble decoy receptor osteoprotegerin are the key regulators of osteoclast differentiation and bone remodeling. Here we show that RANK is also expressed in fully differentiated myotubes and skeletal muscle. Muscle RANK deletion has inotropic effects in denervated, but not in sham, extensor digitorum longus (EDL) muscles preventing the loss of maximum specific force while promoting muscle atrophy, fatigability, and increased proportion o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
52
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(56 citation statements)
references
References 52 publications
3
52
0
1
Order By: Relevance
“…To better understand the influence of RANKL-RANK signaling on muscle cell metabolism, we investigated insulin signaling in C2C12-differentiated myotubes expressing both RANK and RANKL (15,30). In these cells RANKL increased, whereas OPG decreased, the level of IRS1 Ser318 phosphorylation, which is known to downregulate insulin receptor activity, Gastrocnemius and soleus weights were higher under Dmab versus vehicle (increased by 9.3% and 12%, respectively, P < 0.05; Figure 5H).…”
Section: Denosumab Improves Muscle Mass and Strength In Postmenopausamentioning
confidence: 99%
See 2 more Smart Citations
“…To better understand the influence of RANKL-RANK signaling on muscle cell metabolism, we investigated insulin signaling in C2C12-differentiated myotubes expressing both RANK and RANKL (15,30). In these cells RANKL increased, whereas OPG decreased, the level of IRS1 Ser318 phosphorylation, which is known to downregulate insulin receptor activity, Gastrocnemius and soleus weights were higher under Dmab versus vehicle (increased by 9.3% and 12%, respectively, P < 0.05; Figure 5H).…”
Section: Denosumab Improves Muscle Mass and Strength In Postmenopausamentioning
confidence: 99%
“…RANK is also expressed in skeletal muscle and activation of the NF-κB pathway mainly inhibits myogenic differentiation, which leads to skeletal muscle dysfunction and loss (12,13). In turn, OPG-Fc has been shown to reduce inflammation, restore the integrity, and improve the function of dystrophic muscles in a mouse model of Duchenne's muscular dystrophy (mdx mice) (14,15). In this model, RANK/RANKL/OPG controls calcium mobilization and the apoptotic and inflammatory processes (14,15).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, a systemic injection of osteoprotegerin (OPG), a soluble decoy receptor of RANKL, has been shown to restore muscle force and improve muscle histology in dystrophic mdx mice, which have the same dystrophin mutation as human patients . The same research group found that muscle RANK is a key regulator for calcium ion storage and sarco/endoplasmic reticulum Ca 2 +ATPase (SERCA) activity and function of fast‐twitch skeletal muscles . That pathways in addition to RANKL/RANK may play an important role in muscular dystrophy was recently suggested by the observation that full‐length OPG‐Fc was superior to anti‐RANKL in alleviating muscular dystrophy in the mouse model …”
Section: Discussionmentioning
confidence: 98%
“…RANK is also known to be expressed in skeletal muscle. The activation of RANKL/RANK signaling in skeletal muscle leads to the inhibition of myogenic differentiation through the activation of NF-κB, which results in skeletal muscle dysfunction and loss [97]. In fact, administration of the recombinant OPG protein improved muscle strength in a mouse model of Duchenne's muscular dystrophy and denervation-induced muscle atrophy.…”
Section: Muscle Strengthmentioning
confidence: 99%